Pelatihan Penguatan Materi Kesastraan Bagi Dosen Pendidikan Bahasa Indonesia Fakultas Keguruan dan Ilmu Pendidikan Universitas Bumi Persada - Ramli; Budi Arianto; Subhayni; Nurrahmah (Yayasan Kawanad, 2023)
This report discusses the dedication to strengthening literary material for Indonesian Language Education lecturers at FKIP Bumi Persada University. The aim of his service is to increase the understanding and competence of lecturers in teaching and studying Indonesian literature. The initial needs analysis involves surveys and interviews to identify faculty shortages and challenges. The program includes seminars, group discussions, and teaching practice. The results show an increase in lecturers' understanding and competence, enabling the application of more varied teaching methods and more in-depth analysis of literary works. This program provides significant reinforcement of literary material, with a positive impact on teaching and student learning in the field of Indonesian literature. The success of this activity is measured from the process and results of the training. The success of the process is measured by observing several aspects of attitude, such as activeness, cooperation and responsibility. Performance assessment is carried out when participants in groups discuss the results of developing their literary material. Evaluation of activity results is measured based on mastery of training material which includes the results of independent practice, namely compiling Indonesian language literary material.